ANALISIS PEMIKIRAN SYEKH NAWAWI DALAM BIDANG PENDIDIKAN - Bahyati; M.A. Tihami; Umi Kultsum; Dayan Fithoroini (Sekolah Tinggi Agama Islam Nahdlatul Ulama Madiun, 2024)
Sheikh Al-Bantani is the leader of the Islamic Community in the Middle East and Southeast Asia, especially in Indonesia. Apart from being the leader of the Islamic Community, Sheikh Nawawi is also known as an expert scholar in his field, especially in the field of education. So this research was conducted to find out how Sheikh Nawawi thought in the field of education. The research method used is literature study, namely a method of reviewing library literature from various sources to mutually strengthen the descriptions presented. Data analysis uses literature descriptive methods which are carried out objectively so that the results of this research are worthy of being a reference for further research and to enrich the repertoire of Islamic religious education research. The results of the research show that Sheikh Nawawi's educational thought has its own characteristics, namely ta'lim, tarbiyah and ta'dib. Education is not only physical education (practical/charity), but also intellectual, mental/spiritual education for life or long-term education, especially from mahdi to death (lahdi).